Clinical profile of neonatal jaundice patients admitted in a tertiary care hospital in Khulna, Bangladesh - Ali, Md Barkot; Sen, Shantanu; Das, Purnendu Kishor; Islam, Sayma (Mediscope, 2024)
Background: A significant proportion of term and preterm infants develop neonatal jaundice. Jaundice in an otherwise healthy term infant is the most common reason for readmission to the hospital. Therefore, it is necessary to evaluate different aspects of neonatal jaundice in our clinical setup. Objective: The objective of this research was to find out different associated causes, clinical features, and treatment options for neonatal jaundice. Methods: A cross-sectional study was conducted in Gazi Medical College Hospital (GMCH), Khulna, Bangladesh with a total number of 140 neonates with jaundice from January 2018 to January 2021. All data were collected and analyzed prospectively. Convenient purposive sampling was the sampling method. Results: In this study, 79.2% of neonates were full-term and 20.8% were preterm neonates. Physiological jaundice (33.5%) was found as the commonest type. Jaundice with infection was associated with 32.8% of cases. Jaundice with umbilical redness, discharge, and/or foul-smelling (17.9%), and reluctance to feed were commonly associated symptoms. Hepatomegaly and splenomegaly were detected in 7.1% and 3.6% neonates respectively. Phototherapy was given in 61% of cases and 17.8% (25) cases exchange therapy was required. In neonates with physiological jaundice, phototherapy was recommended for most of the cases. In the case of ABO and Rh incompatibility, exchange therapy was required most often along with phototherapy. Conclusion: Physiological jaundice is the most common pattern of neonatal jaundice. Most often, neonatal jaundice may co-exist with neonatal infections. In most cases, phototherapy is required along with or without exchange therapy, depending upon the associated causes and conditions. Mediscope 2024;11(2): 58-61